The hairy fruit = Rambutan ang mabalahibong prutas - Ordinario, Mary Anna (ABC Educational Development Center, 2006)
"Have you seen three sisters with long colorful hair and a bald brother attached to each other? That is how the legend of the Rambutan fruit started. These four children were known to be strange because of their appearance, and unusual because of their attitude. One day, they passed by the Island of Fruits. Find out the harm they did to the fruits and how they learned the value of loving one another."--Back cover.